Direct combustion of recyclable metal fuels for zero-carbon heat and power. (15th December 2015) - Bergthorson, J.M.; Goroshin, S.; Soo, M.J.; Julien, P.; Palecka, J.; Frost, D.L.; Jarvis, D.J.
Graphical abstract: Concept drawing of a metal-fuelled combustor and its possible applications at a range of power-generation scales. Highlights: Metals are promising high-energy density, low-emission, recyclable energy carriers. Metal fuels can be burned with air to produce heat for many applications. A novel combustor that can burn metal fuels is proposed. Metal-oxide combustion products can be captured and recycled. Use of clean power sources to recycle metals enables low-net-carbon emissions. Abstract: It is becoming widely recognized that our society must transition to low-carbon energy systems to combat global climate change, and renewable energy sources are needed to provide energy security in a world with limited fossil-fuel resources. While many clean power-generation solutions have been proposed and are being developed, our ability to transition to a low-carbon society is prevented by the present lack of clean and renewable energy carriers that can replace the crucial roles that fossil fuels play, due to their abundance, convenience and performance, in global energy trade and transportation. Any future low-carbon energy carriers that aim to displace or supplement fossil fuels must have high energy densities for convenient trade and storage, and should be consumable within efficient high-power-density engines for transportation, heavy machinery, and other off-grid energy applications. Hydrogen and batteries have been widely studied but they are not suitable for use as international energy-trading commodities and they cannot provide the energy density and safety demanded by society. Metal fuels, produced using low-carbon recycling systems powered by clean primary energy, such as solar and wind, promise energy densities that are competitive to fossil fuels with low, or even negative, net carbon dioxide emissions. To date, however, few practical high-power-density end-use devices for generating heat or power from metal fuels have been proposed. This paper proposes a novel concept for power generation in which metal fuels are burned with air in a combustor to provide clean, high-grade heat. The metal-fuel combustion heat can be used directly for industrial or residential heating and can also power external-combustion engines, operating on the Rankine or Stirling cycles, or thermo-electric generators over a wide range of power levels. A design concept is proposed for a metal-fuelled combustor that is based upon extensive experimental and theoretical studies of stabilized and propagating metal flames performed at McGill University. This paper also reviews the fundamental and applied aspects of metal-fuel combustion in order to provide the framework needed to assess any potential metal engine technologies. The energy and power densities of the proposed metal-fuelled zero-carbon heat engines are predicted to be close to current fossil-fuelled internal-combustion engines, making them an attractive technology for a future low-carbon society.